2005
DOI: 10.5507/bp.2005.013
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α IN THE DEVELOPMENT OF INSULIN RESISTANCE AND OTHER DISORDERS IN METABOLIC SYNDROME

Abstract: Insulin resistance and obesity are very frequent disorders and are described as the dominant risk factors for cardiovascular disease. The aim of this study was to analyze the interrelations between several metabolic variables (including TNF-α) and factors related to insulin resistance in groups of both normal and hyperlipidemic postmenopausal women and men of appropriate age, and to attempt to elucidate the gender differences. The study was carried out on 70 outpatients of the Metabolic Center. From these, 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 31 publications
8
20
0
Order By: Relevance
“…In this study, the serum concentration of TNF-a, an inflammatory cytokine implicated in IR, was analyzed in individuals diagnosed with or without MS. A significantly increased concentration of TNF-a was found in the MS group, similar to a previously reported study (15). Indeed, several reports indicate that certain dyslipidemias exhibit pro-inflammatory stages that are associated with elevated TNF-a levels (16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the serum concentration of TNF-a, an inflammatory cytokine implicated in IR, was analyzed in individuals diagnosed with or without MS. A significantly increased concentration of TNF-a was found in the MS group, similar to a previously reported study (15). Indeed, several reports indicate that certain dyslipidemias exhibit pro-inflammatory stages that are associated with elevated TNF-a levels (16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, we found that women with MS had significantly higher TNF-a levels compared with the control women, as described previously; however, TNF-a levels did not vary significantly between MS and control men (15). This finding suggests that TNF-a plays an important role in the development of IR in women.…”
Section: Discussionsupporting
confidence: 87%
“…Researches have demonstrated that TNF-α could inhibit exogenous lipid intake and promote fat decomposition simultaneously through inhibiting the activity of lipoprotein lipase in adipocytes, and in this way, TNF-α elevated plasma level of FFA. Blocking TNF-α effect not only increased insulin sensitivity and promoted insulin receptor tyrosine kinase activity but also reduced the plasma FFA level In Zucker rats [13,17], while, in human, TNF-α infusion could increase the level of plasma FFA. All these suggest that exercise ameliorated IR by down-regulating serum TNF-α level and reducing plasma FFA and relieving the lipid deposition [18].…”
Section: Discussionmentioning
confidence: 93%
“…Multiple cytokines, including TNF-α, are involved in the development of IR in the adipose tissue [13,14]. Exercise is proven an important therapeutic method to improve IR in both human and animals [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…As insulin resistance develops, serum leptin increases significantly and the serum concentration of leptin receptors drops 9 . With the development of insulin resistance, the role of TNFα is observed, with the concentration rising in obese individuals with an increase in BMI 10 . These metabolic changes signalize negative clinical consequences.…”
Section: Discussionmentioning
confidence: 99%